Standardization of Cranial Index Measurement in Sagittal Craniosynostosis. Issue 2 (March 2019) - Al-Shaqsi, Sultan Z.; Rai, Ahsan; Forrest, Christopher; Phillips, John
Abstract : N/A: Cranial index is a widely used 2-dimensional measure of skull form. It has traditionally been calculated as a ratio of the maximal cranial width divided by the maximal skull length. Nevertheless, the points of maximal skull length change dramatically in sagittal craniosynostosis due to variable degrees of frontal and occipital bossing. Therefore, such anatomical changes influence the calculated cranial index. Method: This is a retrospective comparative study of 2 methods of measuring cranial index; the traditional method that measures the skull length from glabella to opithcranion versus a modified method that measures the maximal skull length from the most anterior point of the frontal bossing to opithcranion. Cranial indices for 115 patients of radiologically and clinically diagnosed nonsyndromic sagittal craniosynostosis were calculated using both methods. Correlation and Agreements Limits were calculated for comparison between the 2 methods. Results: Males constituted 74.8% (n = 86) of the total sample size with the remaining 29 participants identified as female. The mean age of the study participants was 4.8 months (range 8 days–12 months). The 2 methods were strongly correlated (r = 0.94). The Agreement Limits were calculated to be between 4.02% and 0.18%. Conclusion: Typical anatomical changes such as variable degrees of frontal and occipital bossing influence the accuracy of cranial index measurement in sagittal craniosynostosis. Traditional method of cephalic index measurement could underestimate the severity of scaphocephaly.